2011
DOI: 10.11606/issn.2316-9052.v29i2p135-299
|View full text |Cite
|
Sign up to set email alerts
|

Flora da serra do cipó, Minas Gerais: briófitas (Anthocerotophyta, Bryophyta e Marchantiophyta)

Abstract: -[Flora of Serra do Cipó, Minas Gerais: bryophytes (Anthocerotophyta, Bryophyta and Marchantiophyta)]. In Brazil the bryophyte researches are working in yours states of origin. There are several small floristic works to Brazil but works with a big number of species with descriptions and illustration for all taxa are few. The Serra do Cipó is a high diversity region, and the bryophyte floristic treatment inside the Fanerogamic Flora plan is a great opportunity. This treatment include 237 species and four variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 11 publications
2
22
0
5
Order By: Relevance
“…Fully 89 % of the moss species of the CA had costae and some of those structures were quite broad (ca. 50 % of the surface area of the leaves) (Sharp et al 1994;Yano & Peralta 2011;Santos 2011), including representatives of the genera Octoblepharum, Ochrobryum, and Campylopus. Additionally, accessory pigments that aid in protecting the plants against solar radiation were observed (Seel et al 1992), principally among species of Frullania.…”
Section: Floristics and Geographic Distributionsmentioning
confidence: 99%
“…Fully 89 % of the moss species of the CA had costae and some of those structures were quite broad (ca. 50 % of the surface area of the leaves) (Sharp et al 1994;Yano & Peralta 2011;Santos 2011), including representatives of the genera Octoblepharum, Ochrobryum, and Campylopus. Additionally, accessory pigments that aid in protecting the plants against solar radiation were observed (Seel et al 1992), principally among species of Frullania.…”
Section: Floristics and Geographic Distributionsmentioning
confidence: 99%
“…1), representing about 30% of the number of species of mosses studied by Yano & Peralta (2011). In addition, three new species were recorded for the state of Minas Gerais and 12 more species were identified that have not been cited by Yano & Peralta (2011), but while the latter listed the moss flora of the Serra do Cipó, this paper lists the mosses collected in just one single gallery forest located within the PARNA-Cipó.…”
Section: Resultsmentioning
confidence: 98%
“…This number is very low compared to collection reports of other groups of plants in the same locality that may have involved a greater sampling effort, particularly flowering plants (Madeira et al 2008;Santos et al 2011). After 24 years, a new, much more comprehensive study on bryophytes was conducted in Serra do Cipó produced by Yano & Peralta (2011) containing illustrations, identification keys, and descriptions of 142 species of mosses, 93 species of liverworts, and 2 species of hornworts. The present work is part of the project Flora of Serra do Cipó outlined by Giulietti et al (1987), which has a goal of producing monographs of all plant families of the Serra do Cipó.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As referências usadas para a identificação das espécies foram Frahm (1991), Sharp et al (1994), Buck (1998), Gradstein et al (2001), Gradstein & Costa (2003), Câmara & Costa (2006), Câmara (2008a, b), Ballejos & Bastos (2009), Yano & Peralta (2009), Yano & Peralta (2011) e Bordin & Yano (2013. Os sistemas de classificação adotados foram Renzaglia et al (2009) para Anthocerotophyta, Crandall-Stotler et al (2009 para Marchantiophyta e Goffinet et al (2009) para Bryophyta.…”
Section: Methodsunclassified